for i=0 j=0,1

for i=1 j=0,1

for i=2 j=0,1

1. i=0 ,j=0

*(A[0] + 0) = A[0][0] = 1

2. i=0,j=1

∗ (A[1] + 0) = A[1][0] = 4

3. i=1,j=0

∗ (A[0] + 1) = A[0][1] = 2

4. i=1,j=1

∗ (A[1] + 1) = A[1][1] = 5

5. i=2,j=0

∗ (A[0] + 2) = A[0][2] = 3

3. i=2,j=1

∗ (A[1] + 2) = A[1][2] = 6

is it correct???

for i=1 j=0,1

for i=2 j=0,1

1. i=0 ,j=0

*(A[0] + 0) = A[0][0] = 1

2. i=0,j=1

∗ (A[1] + 0) = A[1][0] = 4

3. i=1,j=0

∗ (A[0] + 1) = A[0][1] = 2

4. i=1,j=1

∗ (A[1] + 1) = A[1][1] = 5

5. i=2,j=0

∗ (A[0] + 2) = A[0][2] = 3

3. i=2,j=1

∗ (A[1] + 2) = A[1][2] = 6

is it correct???